Reformulating the Prohibition of Interfaith Marriage: a Comparative Uṣūl al-Fiqh Analysis in Indonesia and Tunisia (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2025)
This study examines the regulation of interfaith marriage in Indonesia and Tunisia through the analytical framework of Uṣūl al-Fiqh, with particular emphasis on the principles of Maqāṣid al-Sharīʿah (objectives of Islamic law), sadd al-dharīʿah (prevention from harms), and maṣlaḥah mursalah (public interest). Employing normative legal research with a comparative law approach, this study analyzes statutory regulations, judicial practices, fatwas, and classical as well as contemporary Uṣūl al-Fiqh (principles of Islamic jurisprudence) scholarship to understand how Islamic legal reasoning operates within contrasting legislative regimes. The findings demonstrate that Islamic law is epistemically flexible and context-sensitive rather than monolithic. Indonesia adopts a normative–taʿabbudī (religious acts) approach that prioritizes ḥifẓ al-dīn (the protection of religion) and ḥifẓ al-nasl (protection of lineage) through preventive legal measures, whereas Tunisia applies a reconstructive–taʾlīlī (interpretation legal reasoning) approach that foregrounds public welfare and civil justice within a constitutional framework of equality. The study further reveals that these divergent models reflect differing methodological priorities in Uṣūl al-Fiqh shaped by political context, constitutional design, and social pluralism. Theoretically, this research contributes to Islamic legal studies by integrating classical Uṣūl al-Fiqh theory with contemporary socio-legal analysis. Practically, it underscores the need for adaptive marriage regulations that harmonize Sharīʿa objectives with pluralistic social realities while ensuring legal certainty and protection for vulnerable parties. This study recommends strengthening institutional ijtihād (effort) and developing responsive legal guidelines to address interfaith family issues without undermining the foundational principles of Islamic family law.